Preparation and characterization of chitosan and chitosan/gelatin microspheres loaded with chrome and magnesium minerals (Research, Society and Development, 2022)
This work consisted in the preparation and characterization of chitosan (MQUI), chitosan/gelatin (MQUI/GEL), chitosan and chitosan/gelatin microspheres loaded with chromium (MQUI-Cr and MQUI/GEL-Cr) and with magnesium (MQUI-Mg and MQUI-GEL-Mg). The microspheres were prepared by the cross-linked emulsion method using glutaraldehyde as a cross-linking agent. The degree of deacetylation (GD) of chitosan determined by potentiometric titration was 78.7%. The chitosan spectrum in the infrared region showed characteristic bands for this type of material. The images obtained by a digital camera coupled to an optical microscope showed that the MQUI and MQUI-Mg microspheres presented spherical shapes of regular sizes and probably with diameters on a micrometer scale. The addition of 20% of gelatin to chitosan promotes the formation of some microspheres for MQUI/GEL and MQUI/GEL-Mg, but the material starts to present spongy characteristics with the appearance of fibers that seem insoluble. On the other hand, the MQUI-Cr and MQUI/GEL-Cr material could not identify the presence of microspheres, showing aspects of amorphous materials, if in addition to gelatin, the chromium added in the form of sulfate may have influenced the characteristics of this material. The images obtained by Scanning Electron Microscopy confirmed the results obtained by Optical Microscopy, that is, the presence of gelatin caused a fibrous material to appear, and some microspheres embedded in the middle of it or presented materials with amorphous characteristics.